Influence of time elapsed between application and adhesive polymerization on the bond strength to dentin - Carlos José Soares; Gisele Rodrigues Silva; Rodrigo Borges Fonseca; Paulo Sérgio Quagliatto (Universidade Estadual de Campinas, 2015)
The aim of this study was to evaluate the influence of time elapsed between dentin adhesive application and its polymerization on the bond strength to dentin. Superficial bovine dentin received the following treatments: Single Bond (3M/ESPE Dental Products Division, St.Paul, MN, USA), Excite (Ivoclar/Vivadent, Schaan, Liechtenstein), Prime&Bond 2.1 (Dentsply/Caulk, Milford, DE, USA) and One-Up Bond F (Tokuyama Corp.,Tokyo, Japan) being polymerized immediately after its application, 10 and 20 seconds after application. After, indirect composite restoration was fixed with resinous cement RelyX Arc (3M/ESPE). The restoration/tooth interface was observed on Scanning Electron Microscopy (SEM). Bond strength was accessed through a shear bond test on a testing machine at 0.5 mm/min. Data were compared by ANOVA followed by Tukey test (α=0.05). The failure modes was observed by means of stereo-microscope (40X magnification), being classified as adhesive, dentin cohesive, resin cohesive and mixed failure. There was no significant difference on the bond strength between the 10s and 20s groups for the majority of the materials. However, both the failure modes and the SEM showed better interaction between dentin and adhesive systems after elapsed 20s its application. It was concluded that longer periods of adhesive system application resulted on better interaction between dentin and adhesive systems evaluated.